Identification of G-Quadruplex-Binding Inhibitors of Myc Expression through Affinity Selection–Mass Spectrometry. (February 2019) - Flusberg, Deborah A.; Rizvi, Noreen F.; Kutilek, Victoria; Andrews, Christine; Saradjian, Peter; Chamberlin, Chad; Curran, Patrick; Swalm, Brooke; Kattar, Sam; Smith, Graham F.; Dandliker, Peter; Nickbarg, Elliott B.; et al.
The Myc oncogene is overexpressed in many cancers, yet targeting it for cancer therapy has remained elusive. One strategy for inhibition of Myc expression is through stabilization of the G-quadruplex (G4), a G-rich DNA secondary structure found within the Myc promoter; stabilization of G4s has been shown to halt transcription of downstream gene products. Here we used the Automated Ligand Identification System (ALIS), an affinity selection–mass spectrometry method, to identify compounds that bind to the Myc G4 out of a pool of compounds that had previously been shown to inhibit Myc expression in a reporter screen. Using an ALIS-based screen, we identified hits that bound to the Myc G4, a small subset of which bound preferentially relative to G4s from the promoters of five other genes. To determine functionality and specificity of the Myc G4-binding compounds in cell-based assays, we compared inhibition of Myc expression in cells with and without Myc G4 regulation. Several compounds inhibited Myc expression only in the Myc G4-containing line, and one compound was verified to function through Myc G4 binding. Our study demonstrates that ALIS can be used to identify selective nucleic acid-binding compounds from phenotypic screen hits, increasing the pool of drug targets beyond proteins.